2019
DOI: 10.1002/capr.12210
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of accelerated resolution therapy for treatment of post‐traumatic stress disorder: A review and new subgroup analyses

Abstract: Introduction Post‐traumatic stress disorder (PTSD) is a chronic, disabling psychiatric disorder prevalent among civilian and military personnel in the United States (US) and United Kingdom (UK). Current trauma‐focused psychotherapies may place high emotional demands and lengthy treatment commitment that may hinder successful treatment completion for some patients. Accelerated resolution therapy (ART) is an emerging trauma‐focused psychotherapy that is briefer than most current treatments. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Apart from case studies, which predominantly comprised participants of a single sex or gender, none of the articles in this review reported sex- or gender-stratified data. Furthermore, two studies reported findings on men and women but were described as ‘sex’ [ 55 , 56 ] while 12 studies reported findings on males and females but were described as ‘gender’ [ 69 , 74 76 , 85 , 86 , 92 , 95 , 98 , 103 105 ]. Clear reporting of sex and gender data are needed to inform gender transformative integrated care.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from case studies, which predominantly comprised participants of a single sex or gender, none of the articles in this review reported sex- or gender-stratified data. Furthermore, two studies reported findings on men and women but were described as ‘sex’ [ 55 , 56 ] while 12 studies reported findings on males and females but were described as ‘gender’ [ 69 , 74 76 , 85 , 86 , 92 , 95 , 98 , 103 105 ]. Clear reporting of sex and gender data are needed to inform gender transformative integrated care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment protocol of ART may address some of the limitations of the current first-line psychotherapies. ART has a solid theoretical basis (Kip et al, 2014;Kip & Diamond, 2018) and is a promising approach for consideration as an effective trauma-focused treatment modality to meet the specific needs of military service members and veterans who have either never received treatment and or who have treatment-refractory PTSD (Kip et al, 2019;Kip & Diamond, 2018). Thus, the present analysis examines the results of ART used in the treatment of military-related PTSD, with stratification by prior PTSD treatment history, including refractory PTSD following receipt of first-line recommended psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This special section of Counselling and Psychotherapy Research is in the enviable position of being able to showcase some of these cutting edge approaches to working with psychological trauma. The first paper by Kip and Finnegan () introduces a therapeutic approach called Accelerated Resolution Therapy (ART), a brief intervention protocol that is showing promising early results, particularly with military veterans suffering from PTSD and co‐morbid traumatic brain injury (TBI). This approach may particularly spark interest in its prospects, as individuals with TBI generally receive a poorer prognosis regarding PTSD recovery than those without a TBI (Vanderploeg, Belanger, & Curtiss, ).…”
mentioning
confidence: 99%